Pengaruh Pembiayaan Murabahah, KAP dan DPK terhadap Earning After Tax pada Bank Umum Syariah di Indonesia - Sahroni Eka Putra; Guntur Kusuma Wardana (Jurnal Ilmiah Ekonomi Islam, 2022)
Profit or profit is one of the main goals of the establishment of every business entity. Without a profit, the company cannot fulfill its other goal of continuous growth. Profit is an important indicator in measuring the success of a company's performance, so that profit growth in a company can show that the management has succeeded in managing the company's resources effectively and efficiently. One indicator of this profit is net profit after tax. Several things that can affect this profit include the financing carried out, the quality of the assets owned and the funds that can be collected from the community. Based on the above background, this study was conducted to examine and examine the effect of murabahah financing, quality of earning assets and third party funds on net profit after tax of Islamic commercial banks registered with OJK in 2017-2021. Sources of data in this study came from secondary data. The data collection technique uses a study of documentation of the financial statements of the BUS. While the data technique in this study used panel data regression analysis. The results show that murabahah financing, quality of earning assets and third party funds simultaneously have a significant effect on net income after tax on BUS. As for partially, first, murabahah financing has a positive and significant effect on earnings after tax. Second, the quality of earning assets has a negative but not significant effect on earnings after tax. Third, third party funds have a positive and significant effect on earnings after tax.